2019
DOI: 10.1093/aob/mcz179
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Zn accumulation and speciation in kernels of sweetcorn and maize differing in maturity

Abstract: Background and Aims Understanding the speciation of Zn in edible portions of crops helps identify the most effective biofortification strategies to increase the supply of nutrients for improving the health and nutrition of consumers. Methods Kernels of 12 sweetcorn and three maize (Zea mays) varieties were analysed for Zn concentration and content. The speciation of the Zn in the embryos, endosperms and whole kernels at 21, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…In this study, the trends in Zn concentration and Zn content of embryo tissue and the rest of the kernel as the kernels mature on a well pollinated cob of sweetcorn were similar to those observed in earlier studies ( Cheah et al , 2020 ). We showed that the ratio of Zn content in the embryo to Zn content in the rest of the kernel was constant irrespective of the established kernel number, suggesting that there was no preferential storage of Zn in either tissue with increasingly constrained Zn supplies.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the trends in Zn concentration and Zn content of embryo tissue and the rest of the kernel as the kernels mature on a well pollinated cob of sweetcorn were similar to those observed in earlier studies ( Cheah et al , 2020 ). We showed that the ratio of Zn content in the embryo to Zn content in the rest of the kernel was constant irrespective of the established kernel number, suggesting that there was no preferential storage of Zn in either tissue with increasingly constrained Zn supplies.…”
Section: Discussionsupporting
confidence: 89%
“…Post-harvest management and cooking processes can affect the vitamin, mineral and amino acid composition in the final product as compared to raw kernels ( Taleon et al., 2017 ). Since the majority of zinc is located in the maize embryo and pericarp ( Cheah et al., 2020 ) processes that remove large quantities of these two grain structures could reduce the zinc content in the final food product, even below to 10 ​ppm ( Bevis and Hestrin, 2020 ). Processes where not much embryo or pericarp is removed yields high zinc retention ( Bressani et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the trends in Zn concentration and Zn content of both embryo and other kernel constituents as the kernels mature on a well-pollinated cob of sweetcorn were similar to those observed in earlier studies (Cheah et al, 2020). We showed that the ratio of Zn contents in the embryo compared to the rest of the kernel was constant irrespective of established kernel number, suggesting there was no preferential storage of Zn in either tissue with increasingly constrained Zn supply.…”
Section: Accumulation Of Zn and Assimilates In Kernel Constituentssupporting
confidence: 88%
“…Having established the suitability of sweetcorn as a target crop for Zn biofortification, this chapter explores the interactions between genotype and environment that influence the Zn concentration in sweetcorn kernels. Although there is reported data on Zn concentration in mature maize kernels (Lin et al, 2005, Long et al, 2004, Oikeh et al, 2004, few studies have examined Zn concentration in immature kernels of sweetcorn (Warman and Havard, 1998, Cheah et al, 2019a, Cheah et al, 2019b, Cheah et al, 2020. The aim of this study was to quantify immature kernel Zn concentrations across a range of commercial yellow sweetcorn varieties, and contrast this with concentrations in other Zea mays germplasm, including starchy maize lines.…”
Section: Introductionmentioning
confidence: 99%